COMPARISON OF THE EFFECT OF DEXMEDETOMIDINE AND TRAMADOL AS AN ADJUNCT WITH BUPIVACAINE ON THE DURATION OF SPINAL ANESTHESIA - NASEER, H; IQBAL, M; MATEEN, A; ABBAS, SE; FATIMA, N; FARHAN, IA (Biological and Clinical Sciences Research Journal, 2024)
Spinal anesthesia is a commonly employed technique for infra-umbilical surgeries, but its duration is often insufficient for prolonged procedures. Adjuvants such as dexmedetomidine and tramadol are used to enhance its efficacy. Objective: This study aimed to compare the effects of dexmedetomidine and tramadol as adjuvants to bupivacaine in spinal anesthesia. Methods: This randomized controlled trial was conducted at the Department of Anesthesia, AIMC, Jinnah Hospital, Lahore, over one year From 2021 to 2022. 68 patients undergoing elective infraumbilical surgeries were randomized into two groups. Group A received 7 µg dexmedetomidine with 12 mg bupivacaine, and Group B received 25 mg tramadol with 12 mg bupivacaine. Outcomes assessed included the onset of sensory block, total duration of analgesia, time to first rescue analgesia, and intraoperative and postoperative pain scores. Statistical analyses were performed using SPSS version 25, with a p-value <0.05 considered significant. Results: The mean onset of sensory block was significantly shorter in the dexmedetomidine group (6.6 ± 0.603 minutes) compared to the tramadol group (7.2 ± 0.825 minutes; p = 0.002). The total duration of analgesia was significantly longer in the dexmedetomidine group (14.4 ± 1.16 hours) compared to the tramadol group (10.6 ± 1.02 hours; p < 0.001). Similarly, the mean time to first rescue analgesia was significantly prolonged in the dexmedetomidine group (11.8 ± 0.967 hours) compared to the tramadol group (7.9 ± 0.924 hours; p < 0.001). Intraoperative and postoperative pain scores were consistently lower in the dexmedetomidine group, with statistically significant differences at 2, 3, 5, and 6 hours. Conclusion: Dexmedetomidine is a more effective adjuvant than tramadol in spinal anesthesia, offering a shorter onset of sensory block, prolonged analgesic duration, and delayed rescue analgesia with better pain control. These results support the use of dexmedetomidine as a preferred adjuvant for extended surgical procedures under spinal anesthesia. Future studies with larger sample sizes are recommended to validate these findings further.